The effectiveness of developing CLIL-based Indonesian language course teaching materials at Bengkulu city universities - Wulan Febrina; Sudarwan Danim; Didi Yulistio; Ria Ariesta; Abdul Muktadir; Meiselina Irmayanti (LITERA, 2022)
The development of learning materials for Indonesian courses uses a qualitative and quantitative approach to research and development (R D). This study aims to produce teaching materials for Indonesian language courses based on CLIL that follow the learning needs of college students in Bengkulu City. The research subjects were all students who took Indonesian language courses consisting of Bengkulu University, Bengkulu Muhammadiyah University, and Fatmawati Sukarno Bengkulu State Islamic University. The effectiveness test of the development of teaching materials for Indonesian language courses based on CLIL in universities obtained a significant value. The average value of the results before the use of CLIL-based Indonesian language teaching materials in Bengkulu City universities which was developed was 68.50, and a standard deviation of 13,489 and after using CLIL-based Indonesian teaching materials in universities Bengkulu City which has been developed is 80.19 with a standard deviation of 11,546. This means the average difference in student learning outcomes before and after using the development of teaching materials for Indonesian language courses based on CLIL at Bengkulu City Universities.Keywords: teaching materials, Indonesian, CLIL Efektivitas pengembangan bahan ajar bahasa Indonesia berbasis CLIL di perguruan tinggi kota BengkuluAbstractPengembangan bahan ajar mata kuliah Bahasa Indonesia ini menggunakan pendekatan penelitian dan pengembangan (R D) dengan metode kualitatif dan kuantitatif. Penelitian ini bertujuan untuk menghasilkan bahan ajar mata kuliah bahasa Indonesia berbasis CLIL yang sesuai dengan kebutuhan belajar mahasiswa perguruan tinggi di Kota Bengkulu. Subjek penelitian adalah seluruh mahasiswa yang mengambil mata kuliah bahasa Indonesia yang terdiri dari Universitas Bengkulu, Universitas Muhammadiyah Bengkulu, dan Universitas Islam Negeri Fatmawati Soekarno Bengkulu. Uji efektivitas pengembangan bahan ajar mata kuliah bahasa Indonesia berbasis CLIL di perguruan tinggi memperoleh nilai yang signifikan. Nilai rata-rata hasil sebelum penggunaan bahan ajar bahasa Indonesia berbasis CLIL di perguruan tinggi Kota Bengkulu yang dikembangkan adalah 68,50, dan standar deviasi 13.489 dan setelah menggunakan bahan ajar bahasa Indonesia berbasis CLIL di perguruan tinggi Kota Bengkulu yang telah dikembangkan adalah 80,19 dengan standar deviasi 11.546. Hal ini berarti terdapat perbedaan rata-rata hasil belajar mahasiswa sebelum dan sesudah menggunakan pengembangan bahan ajar mata kuliah bahasa Indonesia berbasis CLIL di Perguruan Tinggi Kota Bengkulu.Kata kunci: ajar, bahasa Indonesia, CLIL